Peran Dinamika Monsun terhadap Konsentrasi PM2.5 selama Peristiwa El Niño 2023–2024 di Asia Tenggara: Sebuah Isu Kesehatan Masyarakat - Sari, Putri Nilam; Putri, Ade Suzana Eka; Yudison, Adyati Pradini; Nursal, Dien Gusta Anggraini; Firdani, Fea (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2026)
Background: El Niño and positive Indian Ocean Dipole (IOD) events can disrupt monsoon circulation and increase air pollution exposure in Southeast Asia, particularly PM2.5, which poses significant public health risks. Objective: This study aimed to analyze PM2.5 exposure during the 2023–2024 El Niño period and assess its potential public health risks in Southeast Asia. Methods: Daily PM2.5 concentrations in major Southeast Asian capitals during the 2023–2024 El Niño period were analyzed to evaluate temporal variability, exceedances of WHO and national standards, and potential transboundary pollution using Spearman correlation analysis. Results: Jakarta and Hanoi showed the highest daily median PM2.5 concentrations, exceeding 100 µg/m3. However, exceedances of WHO and national air quality standards occurred in almost all ASEAN capitals. Strong positive correlations were observed between Yangon and Vientiane (r = 0.753, p < 0.01), Vientiane and Bangkok (r = 0.695, p < 0.01), and Yangon and Bangkok (r = 0.670, p < 0.01), likely due to shared continental and monsoonal influences. In contrast, weaker correlations were found among maritime cities such as Jakarta, Singapore, and Kuala Lumpur because of variable sea–land circulation and tropical convection. Elevated PM2.5 concentrations during El Niño may increase respiratory and cardiovascular health risks. Conclusion: PM2.5 concentrations during the 2023–2024 El Niño period exceeded WHO and national standards in most Southeast Asian capitals, highlighting the need for cross-border mitigation strategies and integrated early warning systems to protect public health.